Bioanode-Assisted Removal of Hg2+ at the Cathode of Microbial Fuel Cells - Kumar, Rohit; Yadav, Sukrampal; Patil, Sunil A. (American Society of Civil Engineers, 2020)
The removal of heavy metals from contaminated waters is highly desirable to circumvent their toxic effects on the ecosystem and human health. In this study, we report on the bioanode-assisted removal of mercury (Hg2+) at the cathode of microbial fuel cells (MFCs). An anode with an acetate-grown microbial electroactive biofilm, referred to as a bioanode, was used to facilitate the reduction of Hg2+ ions at the cathode of two-chambered MFCs. The MFCs with only Hg2+ as an electron acceptor achieved an open-circuit voltage of 778 ± 18.4 mV and a power density of 32.6 ± 0.5 mW/m2. Up to 98% Hg2+ removal efficiency at a rate of 0.4 mg/L/h, from an initial 10 mg/L to the final 0.2 mg/L Hg2+ concentration in the catholyte, was achieved in 24-h tests. Inductively-coupled plasma mass spectrometry analysis revealed deposition of up to 8.84 mg/L of Hg at the cathode surface. Even a low Hg2+ concentration of 0.270 mg/L was removed efficiently at a rate of 0.19 mg/L/h by the MFCs. The cathode potential changed according to the concentration or availability of Hg2+ in the catholyte.
Keywords: Bioelectrochemical systems; Electrode-assisted bioremediation; Mercury removal; Microbial electroactive biofilm